PEDAGOGIKALÍQ ISKERLIKTE KOMMUNIKATIV KOMPETENCIYA - Abdiev, B. (SCIENCE and SOCIETY, 2025)
The article examines the essence of the concept of communicative competence, its definition in dictionaries, its pedagogical significance, and the possibilities and current state of the educational system aimed at its formation. Also, the organizational and legal foundations of the development are also covered of communicative worldview and thinking, and the state of legal norms in practice. For this purpose, it is appropriate to clarify the content of the concept of competence first.